(untitled) - Madeo, Angela (London, 2015)
This book focuses on the continuum mechanical modeling of artificial and natural micro-structured materials by means of Generalized Continuum Theories
Keywords: Continuum mechanics.,Mechanics, Applied.,Vật lý ứng dụng